Compartmentation of multiple metabolic enzymes and their preparation in vitro and in cellulo - Ito-Harashima, Sayoko; Miura, Natsuko (Biochimica et biophysica acta. General subjects, 2025)
Compartmentalization of multiple enzymes in cellulo and in vitro is a means of controlling the cascade reaction of metabolic enzymes. The compartmentation of enzymes through liquid–liquid phase separation may facilitate the reversible control of biocatalytic cascade reactions, thereby reducing the transcriptional and translational burden. This has attracted attention as a potential application in bioproduction. Recent research has demonstrated the existence and regulatory mechanisms of various enzyme compartments within cells. Mounting evidence suggests that enzyme compartmentation allows in vitro and in vivo regulation of cellular metabolism. However, the comprehensive regulatory mechanisms of enzyme condensates in cells and ideal organization of cellular systems remain unknown. This review provides an overview of the recent progress in multiple enzyme compartmentation in cells and summarizes strategies to reconstruct multiple enzyme assemblies in vitro and in cellulo. By examining parallel examples, we have evaluated the consensus and future perspectives of enzyme condensation. •This study summarized the regulation of intracellular assembly of multiple enzymes.•Various enzymes can be sequestered into coacervate droplets in vitro.•Enzymatic activity is likely enhanced in the enzyme droplets assembled in vitro.•Artificial enzyme compartmentation in cells enables the control of enzyme activity.